Die Sozialgruppe der Mulattieri im Apennin - Kühne, Ingo (ERDKUNDE, 1970)
The Mulattieri maintain, in many respects, a special standing among the life-styles of the Apennines. Although they originally performed very varied transport functions with their mules, modern transport development has reduced them mainly to timber transport in impassable country. The Butteri form a special sub-group, accompanying the large flocks of sheep. This specialisation and the existence of seasonal and regional variations in the volume of timber production forces the Mulattieri of the mountains to winter and, for most, summer migration as well often over great distances. As an independent entrepreneur and owner of his beasts of burden, the Mulattiere works mostly without hired help for earnings which, especially for the Abruzzi, are very meagre. The living conditions of the Mulattieri in their migratory work resemble, in their most primitive simplicity, those of the wandering shepherds. The antiquity of their work style differentiates them particularly from all the related transport trades which were forced to adapt themselves to contemporary requirements as part of the technological process. In the last 20 years the number of Mulattieri has been sharply reduced, especially in the north west Apennines. A general decrease of employment possibilities is the cause of this decline. Development of the transport system, the disappearance of charcoal transport, the transformation of the woodlands and the establishment of State Forests have all been contributory factors. The main settlement areas of the Mulattieri today lie in the middle Apennines from the Romagna to the Abruzzi and their working areas stretch north to the Alps.